2008
DOI: 10.1073/pnas.0802432105
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and genomic evolution under constant cold in Antarctic notothenioid fish

Abstract: The antifreeze glycoprotein-fortified Antarctic notothenioid fishes comprise the predominant fish suborder in the isolated frigid Southern Ocean. Their ecological success undoubtedly entailed evolutionary acquisition of a full suite of cold-stable functions besides antifreeze protection. Prior studies of adaptive changes in these teleost fishes generally examined a single genotype or phenotype. We report here the genome-wide investigations of transcriptional and genomic changes associated with Antarctic nototh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
226
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(244 citation statements)
references
References 39 publications
16
226
2
Order By: Relevance
“…To identify candidate cold tolerance-related and cold change-related genes, a large-scale EST sequencing of multi-tissues including brain, liver, head kidney, and ovary had been performed in Antarctic notothenioid (Dissostichus mawsoni), and some important cold-specific expressed genes had been identified by comparative transcriptome analyses between D. mawsoni and non-notothenioid warm-water teleost fishes [133,134]. Moreover, the molecular origination of antifreeze protein III (AFP III) was demonstrated to come from a duplicate copy of sialic acid synthase (SAS) gene, supporting the evolutionary mechanism by neofunctionalization under escape from adaptive conflict [135].…”
Section: Cold Tolerance Trait and Candidate Cold Tolerancerelated Genesmentioning
confidence: 99%
“…To identify candidate cold tolerance-related and cold change-related genes, a large-scale EST sequencing of multi-tissues including brain, liver, head kidney, and ovary had been performed in Antarctic notothenioid (Dissostichus mawsoni), and some important cold-specific expressed genes had been identified by comparative transcriptome analyses between D. mawsoni and non-notothenioid warm-water teleost fishes [133,134]. Moreover, the molecular origination of antifreeze protein III (AFP III) was demonstrated to come from a duplicate copy of sialic acid synthase (SAS) gene, supporting the evolutionary mechanism by neofunctionalization under escape from adaptive conflict [135].…”
Section: Cold Tolerance Trait and Candidate Cold Tolerancerelated Genesmentioning
confidence: 99%
“…They employed array comparative genomic hybridizations (aCGH) to compare gene copy number at 10 700 loci in three Antarctic and two non-Antarctic notothenioid fishes. Using a hybridization threshold ratio set for a single, known, gene duplication event between two of these species, Chen et al (2008) identified 101 protein-coding genes for which the average hybridization ratio across the cold-adapted species was above this threshold-indicating likely gene duplication. These candidate loci include 15 with potential activity in cold response, and many that were also among those upregulated in D. mawsoni relative to temperate species according to the EST analysis ( Figure 1).…”
mentioning
confidence: 99%
“…These candidate loci include 15 with potential activity in cold response, and many that were also among those upregulated in D. mawsoni relative to temperate species according to the EST analysis ( Figure 1). It is perhaps unusual to apply a threshold analysis technique to this experiment, as Chen et al (2008) do, rather than a statistical analysis that is more appropriate to the hybridization design. A more rigorous statistical analysis of aCGH results would help to quantify hybridization variation within and between species and ecotypes (for example, Emerson et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations